The use of ICT among pre-service English language teachers - Tam, Suet Yet; Noordin, Nooreen (Macrothink Institute, 2017)
Information Communications and Technology (ICT) was first introduced through the Smart School project in 1997.Results from past studies on teachers’ use of ICT were mixed whereby their confidence in using ICT and their use and integration of ICT in their classroom practice were incoherent. Hence, this study intends to investigate the confidence level and skills of current pre-service teachers in teaching the English language through the use of ICT. Forty six pre-service English language teachers were selected purposively from a local university and a teacher training college, based on these few criteria set within the limitations of this study. This study adopted and adapted the questionnaires from the ICT Integration Survey (Spazak, 2010) and Technological Pedagogical and Content Knowledge (TPACK) by Mishra and Koehler (2006). These questionnaires are adopte for the purpose of understanding the pre-service teachers’ technological skills, as well as their content and pedagogical knowledge of English language teaching at the point in time when the data was collected. The data collected were analysed using the Statistical Packet for the Social Sciences (SPSS). Results showed that pre-service English language teachers are confident users of ICT, both for their own personal interests and to integrate ICT in their teaching. However, it is also found that pre-service teachers are skilled in ICT because they have been exposed to it since young. Further results that have emerged from this study revealed that there is no relationship between the time used in ICT and the confidence or skills in using ICT.